Comparative Characterization of Sequence Structure, Gene Expression, and Enzyme Activity of Alpha‐2‐macroglobulin between Stichopus monotuberculatus (Stichopodidae) and Holothuria atra (Holothuriidae). Issue 2 (5th July 2016) - Qian, Jing; Ren, Chunhua; Xia, Jianjun; Yu, Zonghe; Hu, Chaoqun
Abstract: Alpha‐2‐macroglobulin (A2 M) is essential for hosts defending against pathogen infections. In this study, two distinct A2 Ms were identified from sea cucumbers Stichopus monotuberculatus and Holothuria atra, which belong to different genera in the Phylum Echinodermata, and named StmA2 M and HaA2 M, respectively. Structural analysis of StmA2 M and HaA2 M revealed that all contain the bait region domain, thioester domain, and receptor‐binding domain. Phylogenetic analysis indicated that StmA2 M and HaA2 M all belong to the echinoderm A2 Ms. The cleavage site RXXR and the catalytic histidine residue for complement component C3 were found in StmA2 M and HaA2 M. Compared with human A2 M, the three‐dimensional structures of StmA2 M and HaA2 M were more similar to that of common carp A2 M. Both StmA2 M and HaA2 M showed the strongest response at transcriptional levels to lipopolysaccharide (LPS) at 12 h and polyriboinosinic polyribocytidylic acid [Poly (I: C)] at 24 h, respectively. Activity of StmA2 M showed the strongest response to Poly (I: C) at 6 h, while the strongest change of HaA2 M activity was induced by LPS at 24 h. The differential mRNA expression and enzyme activity levels suggested that A2 M in sea cucumbers might be involved in different immune responses to LPS or Poly (I: C) challenge.